Surface Modification of Hematite using Stearic Acid as Hydrophobic Inorganic Pigment Materials - Iqbal, Rendy Muhamad; Agnestisia, Retno; Damsyik, Akhmad; Sinaga, Tiara Cristy Agatha; Khaerudini, Deni Shidqi; Wulandari, Ika Octavia; Susanti, Indri; Putra, Riandy; F. Adany (BRIN Publishing (Penerbit BRIN), 2025)
The inorganic pigment is a material that determines the color of a paint that can be used as a coating material. Until now, the basic material for red pigment, namely hematite, has been imported to meet domestic needs. This study aims to develop a hematite-based inorganic pigment material from the mill-scale waste of PT Krakatau Steel by modifying the surface to be hydrophobic, making the pigmenting material resistant to acid attack and preventing peeling and corrosion of the material. The surface modification of hematite is carried out by reacting it with stearic acid into ethanol as a solvent. Hematite was immersed in a stearic acid solution with various concentrations of 2, 4, 6, and 8% for 6 hours; it was then separated by filtration and followed by the drying process. The hematite-stearic was characterized by X-ray diffraction (XRD), Fourier-transform infrared (FTIR), scanning electron microscope (SEM), and water contact angle (WCA). The results show that the grafting process successfully changed the properties of hematite to hydrophobic. It is also supported by the FTIR spectrum due to the presence of molecular vibration of C-H, C=O, C-O, and Fe-O. Then, the higher contact angle is 150.474° for the stearic acid concentration of 6%.